A Painless Restricted Motion of the Thumb: What Etiology? About An Uncommon Tumor in Uncommon Localization - Naoufal Elghoul; Mohammed Benchakroun; Azzelarab Bennis; Omar Zaddoug; Ali Zine; Mansour Tanane; Abdeloihab Jaafar (Case Reports in Orthopedics)
Lipomas in fingers are rare and account for less than 1% of all cases. As a type of lipoma, the spindle cell lipoma is exceptional and it presents 1.5% of total adipocyte tumors. Moreover, its localization in the thumb is extremely rare. Only three cases have already been reported in adults; our case constitutes the fourth case, which is about a 61-year-old female who presented since 18 months a mass on the ulnar lateral aspect of the thumb. After clinical and radiological assessments, an entire excisional biopsy of the mass was performed. The histopathological analysis confirmed the spindle cell lipoma of the thumb. At the last follow-up of two years, the patient did well with no recurrence and no restricted motion of the thumb. So, although lipomas of the digit are rare, they should be considered a possible etiology of either painful or mechanic restricted motion of the digit.